Efektivitas Video Pembelajaran Canva untuk Mengidentifikasi Unsur Intrinsik Teks Cerpen di Sekolah Menengah Pertama - Utami, Dewi Wahyu; Ananda, Ifa Chairin; Zaliarisma, Nanda Yogi; Suprihatiningsih, Riyana; Ulya, Chafit (Lingua Franca, 2022)
Learning media is a tool needed by teachers in supporting and supporting teaching and learning activities in schools. This study aims to prove the effectiveness of learning videos using the Canva application in identifying the building blocks of short stories at SMP Negeri 1 Baturetno. The research method used is a descriptive quantitative research method and data collection techniques using questionnaires by students. From this study, it was found that the learning media used in the basic competencies of short stories at SMP Negeri 1 Baturetno before using Canva's learning videos were Google Meet and Whatsapp voice notes. Of the two learning media, students prefer the Google Meet application for teaching and learning activities. This can be seen in 76.7% of students having more understanding of the material being taught and as many as 81.4% of students being more active when teachers teach using Google Meet. After using Canva's learning video, 93.1% of students stated that the learning media was fun, there were no significant obstacles in its use, and the learning video was suitable for further learning. Thus, it can be concluded that Canva's learning videos are effectively used in learning Indonesian basic short stories competence at SMP Negeri 1 Baturetno.